New Protectionism, Sanctions and EU Disintegration: Challenges for Baltic Trade - Laaser, Claus Friedrich; Schrader, Klaus (Estonian Discussions on Economic Policy, 2018)
Against the backdrop of the Estonian Presidency of the Council of the European Union in the second half of 2017 the authors propose to focus the political agenda on the threats to free trade which emerged by the protectionist views of the Trump government, the imminent weakening of the EU Common Market in course of the Brexit and the still lingering conflict with Russia which is accompanied by trade sanctions. The authors show how far the three Baltic States depend on trade with Russia, the United Kingdom and the USA by a share analysis of disaggregated trade flows and a gravity analysis of trade relations. The analyses reveal that Estonia, Latvia and Lithuania could be affected negatively by all the three challenges to the free movements of goods and services. While they are still trading over-proportionally with Russia the attractiveness of UK and US markets for Baltic enterprises is already visible and these markets offer further development potential. Hence, the promotion of the concept of open markets would not only help bridging political divides but it would also foster the Baltic States’ gains from globalization and would reduce economic and political dependencies